Ethical, responsibility and environmental solidarity - Naime, Roberto; Malmann, Fernanda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article is an approach to the current state of the theme of responsibility, ethics and environmental solidarity, the light of the theory of risk of Ulrich Beck and seeking ways to verify the contribution that positivization rights can contribute to the current state of the subject. There is a focus on determining the need for preservation of environmental features for the enjoyment of future generations in terms of maintenance of environmental quality which may be decisive in the quality of life of future generations, to approach from the right in intergenerational environmental theme, framed by characteristics imposed by the risk society.